THE RESILIENCE OF FISHERMAN COMMUNITIES IN RESPONDING CLIMATE CHANGE: A CASE STUDY IN GRAJAGAN PANTAI VILLAGE, BANYUWANGI, EAST JAVA - Ary Wahyono; Masyhuri Imron; Ibnu Nadzir (Jurnal Masyarakat dan Budaya, 2014)
Fishermen are the most vulnerable social community against the climate change. Marine environment change directly influences their livelihood system. This paper aims to discuss the extend of resilience of the fisherman communities in the coastal of Grajagan Village, Banyuwangi, East Java, in responding the impacts of climate change. To understand the resilience of fisherman communities, this paper compares the fishing unit typology and the working characteristics from various fisherman communities in responding the climate change impacts. Finding of this research shows that there is different resilience strategy among different fishing units, namely Slerek, Payang, and Jukung. The jukung fisherman community has a better resilience in responding the climate change impacts compared to the Slerek and Payang fisherman communities. The jukung fisherman community has various fishing units, which can be operated in different seasons.